2009
DOI: 10.4314/jasr.v8i2.43343
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Participation Of Outgrowers In Certified Hybrid Maize Seed Production In Giwa Local Government Area Of Kaduna State And Its Policy Implication For Food Security

Abstract: The study analyzed factors that influence farmer's participation in hybrid maize seed production in the study area. A Logit analysis was used to analyze factors influencing farmer's participation in hybrid maize seed production while T-test was used to analyze if there is difference in the mean yields of farmers growing hybrid seeds and those involved in local maize production. Structured questionnaire was used to collect data from farmers based on the 2005 cropping season activities while on the spot observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…This implies that older farmers with relatively larger farm sizes are more likely to participate in the input credit scheme. This finding is consistent with Denkyirah et al (2016) and Omolehin et al (2008), who found that age of farmers positively contributed to participation in input support schemes in Ghana and Nigeria, respectively.…”
Section: Awareness and Participationsupporting
confidence: 90%
See 1 more Smart Citation
“…This implies that older farmers with relatively larger farm sizes are more likely to participate in the input credit scheme. This finding is consistent with Denkyirah et al (2016) and Omolehin et al (2008), who found that age of farmers positively contributed to participation in input support schemes in Ghana and Nigeria, respectively.…”
Section: Awareness and Participationsupporting
confidence: 90%
“…Age – Several studies demonstrate a positive relationship between age and participation in credit schemes by farmers. Denkyirah et al (2016) and Omolehin et al (2008) found that age of farmers positively contributed to participation in credit support schemes. Mamuye (2021) also reported similar results.…”
Section: Literature Reviewmentioning
confidence: 99%